STRATEGI KEPALA DESA DALAM MENANGGULANGI KEMISKIN DI DESA RANGALAKA - Rusli Hereng; Chusnul Mar'iyah Mahmud; Berlian Hamsa; Rustam Pratama Putra; Sundari (LPPM Universitas Madako Tolitoli, 2026)
This study aims to describe the strategies employed by the Village Head of Rangalaka in tackling extreme poverty in Rangalaka Village, Kotabaru Subdistrict, Ende Regency, East Nusa Tenggara. A descriptive qualitative approach was used in this study, with data collection techniques including interviews, observation, and documentation of the Village Head, village officials, community leaders, and program beneficiaries. The results of the study show that the Head of Rangalaka Village implemented four main strategies in combating extreme poverty, namely: (1) distribution of assistance and social security through the BLT-DD, BPNT, KIS, and KIP programs; (2) community economic empowerment through the establishment of BUMDes and training in productive business skills; (3) improving human resource capacity through entrepreneurship and financial management training; and (4) optimizing Village Funds for productive economic activities. Factors supporting the success of these strategies include community and traditional leader support, budget transparency, and synergy with cross-sector institutions. However, obstacles include low education levels, limited capital, and dependence on government assistance. Overall, the strategy of the Rangalaka Village Head demonstrates a community-based development approach that is oriented towards the economic empowerment and independence of residents. This approach is in line with national policies and sustainable development goals (SDGs), particularly in efforts to eradicate extreme poverty at the village level.